KIPCHAKS IN THE SOUTH CAUCASUS: AN EPISODE FROM THE BIOGRAPHY OF KHWARAZMSHAH JALAL AL-DIN MANGBURNI - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2024)
In the composition of the 13th-century Persian historical work, “Tarikh-i Jahangushay,” authored by ʻAlaʼ al-Din Ata-Malik Juvaini and well-known among specialists, there exists a noteworthy episode within the narrative detailing the aggressive campaigns of Khwarazmshah Jalal al-Din Mangburni in the South Caucasus. This episode refers to the encounter between the Khwarezmians and the Georgian army. According to the Persian historian, the Georgian army, alongside other ethnic groups, included a detachment of Kipchaks numbering twenty thousand men. Prior to the battle, the Khwarazmshah dispatched an embassy to them, which, through persuasion, convinced the Kipchak detachment not to engage in combat with Jalal ad-Din and his forces but to withdraw from the battlefield. This diplomatic intervention significantly contributed to the victory of the Khwarezmian army. Although the episode from the text “Tarikh-i Jahangushay” is recognized by scholars, there has been a lack of dedicated research in global academia focused on analyzing the genesis of this narrative and its historical veracity. In our presented article, we not only endeavor to dissect Juvaini’s account concerning the Kipchaks and their involvement in the referenced battle between the Georgian army and the Khwarezmians, but also elucidate the interconnections between this narrative and other earlier and subsequent Arab-Persian historiographical works. The study highlights the migration of the Kipchaks to the South Caucasus region both before the Mongol period and during the 1220s, correlating reports of such migrations with Juvaini’s assertions. Among the most significant findings of our study is the alignment of the Persian historian’s narrative with historical realities, underscoring the distinctive rapport between the Khwarazmshah and the elite of the Kipchak tribal confederation, which had its roots in the pre-Mongol era.